2009
DOI: 10.1152/ajpheart.00509.2009
|View full text |Cite
|
Sign up to set email alerts
|

Reflex vasoconstriction in aged human skin increasingly relies on Rho kinase-dependent mechanisms during whole body cooling

Abstract: WL. Reflex vasoconstriction in aged human skin increasingly relies on Rho kinase-dependent mechanisms during whole body cooling. Am J Physiol Heart Circ Physiol 297: H1792-H1797, 2009. First published August 28, 2009 doi:10.1152/ajpheart.00509.2009.-Primary human aging may be associated with augmented Rho kinase (ROCK)-mediated contraction of vascular smooth muscle and ROCK-mediated inhibition of nitric oxide synthase (NOS). We hypothesized that the contribution of ROCK to reflex vasoconstriction (VC) is grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
4
27
0
Order By: Relevance
“…Although the reason for these disparate findings remains unclear, differences may be related to varied methodology of the cooling perturbation, because the intensity and populations of thermal and/or pain receptors stimulated by the cooling para- digm are known to influence sympathetic outflow. To this end, the present investigation examined sympathetic nervous system activation in healthy young and older adults using a standardized whole body skin surface cooling protocol via water-perfused suit (3,30,51,55). Consistent with a wide body of literature examining MSNA at rest in older adults at thermoneutrality (27,39,53), older adults in the present study exhibited increases in basal muscle sympathetic outflow.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Although the reason for these disparate findings remains unclear, differences may be related to varied methodology of the cooling perturbation, because the intensity and populations of thermal and/or pain receptors stimulated by the cooling para- digm are known to influence sympathetic outflow. To this end, the present investigation examined sympathetic nervous system activation in healthy young and older adults using a standardized whole body skin surface cooling protocol via water-perfused suit (3,30,51,55). Consistent with a wide body of literature examining MSNA at rest in older adults at thermoneutrality (27,39,53), older adults in the present study exhibited increases in basal muscle sympathetic outflow.…”
Section: Discussionsupporting
confidence: 60%
“…Importantly, whole body cooling elicits significant visceral (celiac, superior mesenteric, and renal vascular conductance indexes) and peripheral (brachial artery, total forearm, and CVC) vasoconstriction that contributes to sustained increases in BP throughout cooling in young adults (62). Reflex peripheral cutaneous vasoconstriction is significantly impaired in aged adults (30,51,55). While the visceral vasoconstrictor responses to cold stress have not been examined in older adults, it is interesting to note that the splanchnic vasoconstrictor responses to upright tilt are greater in older compared with young subjects (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficits in noradrenergic function have also been identified in adrenoreceptor and second messenger systems of vascular smooth muscle (7,18,26,34,36). Conflicting accounts exist regarding the effect of age on the cutaneous VC response to NE: one study showed no difference (40) and another demonstrated a blunted VC response in aged skin (36).…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly relevant to aged skin considering recent evidence indicating that rho-kinase, which is directly stimulated by ROS, mediates ϳ50% of the reflex VC response in older adults (26). Additionally, BH 4 minimizes NOS-derived ROS by preventing enzymatic uncoupling (19,29).…”
mentioning
confidence: 98%